ANALISIS PENERAPAN TEKNIK SQ3R DALAM PEMBELAJARAN MEMBACA BAHASA INGGRIS PADA SISWA SMP - Yessica E Sinabariba; Friscilla Sembiring; Immanuel Padang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of the SQ3R (Survey, Question, Read, Recite, Review) technique in teaching English reading to junior high school students. The research was motivated by students’ low reading comprehension skills, which are influenced by limited vocabulary, low reading interest, and the use of less varied instructional strategies. This study employed a descriptive qualitative approach involving eighth-grade students and an English teacher as research participants. Data were collected through classroom observations, interviews, and documentation and were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings indicate that the SQ3R technique can be implemented systematically through its five stages: survey, question, read, recite, and review. The implementation of this technique enhances students’ participation in the learning process, improves their reading comprehension, and encourages more critical and structured thinking. However, several challenges were identified, including limited vocabulary, difficulties in formulating questions in English, and students’ lack of confidence in retelling the content of the text. Overall, the SQ3R technique can serve as an effective instructional strategy to improve English reading comprehension among junior high school students.